CHANGES IN PROTEIN SULFHYDRYLS, PROTEIN CARBONYLS AND LIPID PEROXIDATION LEVELS IN SERA OF PATIENTS WITH RHEUMATOID ARTHRITIS: CORRELATION WITH DISEASE ACTIVITY - Mustafa Serteser; Deniz Evcik; Tülay Köken; Ahmet Kahraman (Archives of Rheumatology, 2006)
Objective: Reactive Oxygen Species (ROS) play a major role in the generation of acute and chronic inflammatory processes one of which is rheumatoid arthritis (RA). Patients and Methods: This study was designed to investigate ROS and antioxidant affects in RA patients. The antioxidant activity was determined by measuring total protein sulfhydryl (SH) levels. ROS was indicated by measuring protein carbonyls and malondialdehyde (MDA) levels. A total of 29 RA patients aged between 31 to 68 years old were recruited. Also 20 control subjects were selected from healthy individuals Total protein SH, protein carbonyls and MDA levels were measured from sera of both groups. Results: Total protein SH levels of RA patients were found to be significantly decreased than those found in control group (396,26±42,33 mmol/L vs 677,21±59,98 mmol/L, p<0,001). Also the levels of protein carbonyls and MDA were found to be statistically increased in RA patients respectively (105,45±14,26 mmol/L vs 93,65±10,49 mmol/L, p<0,05, 14,51±2,28 mmol/L vs 5,56±1,25 mmol/L, p<0,001). Patients active in disease had higher levels of MDA and lower levels of total protein SH levels when compared to those patients in remission. A negative correlation was found between protein carbonyls and erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) (r=-0,415, p<0,05, r=-0,687, p<0,001) in RA patients. No correlation was found in patients active in disease but negative corelation was found between protein carbonyls and ESR and CRP in patients in remission. Conclusion: In conclusion the level of ROS seems to increase and measurement of these markers may give us information about inflammatory process in RA. (Rheumatism 2006; 21: 18-22)